THE OPTIMISTIC SYMBOLISMS IN ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA - Adi Kusuma and Citra Anggia Putri (LINGUISTICA, 2018)
This study aims at explaining the symbols used in the novel and describing the values of optimistic reflected in the symbols used in Hemingway’s The Old man and The Sea. This research is classified as a descriptive qualitative method. The primary data source of this study is the novel The Old Man and the sea by Ernest Hemingway. The collecting data process is note-taking technique. This study is also categorized as library research. Based on the findings and discussion, the researcher draws the conclusion such follow. First, it is found that there are eight symbols used in this novel. They are classified into Individual symbol and Universal symbol. In the novel the Old Man and the Sea the symbols which the researcher considers as individual symbols. Individual symbols are the old man as a symbol of someone who has optimistic, Manolin as a symbol of hope, Marlin as a symbol Struggle of life, Shark as a symbol of Destruction and problem, joe Di Maggio as a symbol Strong desire, bird as a symbol of help. The second category is Universal symbol. universal symbol are Sea as symbol of universe, Lion as symbol of strength. there are two elements or values which characterize someone as the one who has optimistic life which is reflected in the symbols used in this novel. They are the values of struggle and positive thinking, Second, Those symbols reflect the values of optimistic life which is to be the theme of the novel.